Career trajectories and employment outcomes of Iceland School of Energy alumni - Jacob Ristagno Kaminski 1996- (2024)
This thesis examines the career trajectories and employment outcomes of graduates from the Iceland School of Energy (ISE) at Reykjavik University (RU), providing a detailed analysis of their professional advancements within the global sustainable energy and sustainability sectors. Employing a mixed-methods approach, and utilizes quantitative data from university records and alumni profiles, complemented by qualitative insights derived from historical analysis and discussions with stakeholders shows that ISE alumni have effectively entered a range of sectors, with 30% entering utilities, 25% in professional scientific and technical services, and 18% pursuing advanced studies, primarily PhDs, in educational services. The remaining students have entered a variety of sectors, further demonstrating the versatility and adaptability of ISE graduates in the job market. Additionally, graduates have demonstrated significant geographical mobility, with 25% of international students remaining in Iceland, 20% moving to other countries, and 55% returning to their home countries, thereby disseminating knowledge acquired in their studies in Iceland. Key challenges encountered across the sustainable energy education curriculum include accommodating diverse backgrounds, curriculum development to encompass the breadth of sustainable energy topics, fostering industry collaboration within the sustainability sector, addressing diversity, and overcoming administrative challenges. This thesis contributes to the body of knowledge on sustainable energy education by showing its impact on career development and offering strategic recommendations for program development to better equip students for the sustainable energy and sustainability sectors. Þessi ritgerð fjallar um starfsferil og atvinnuárangur útskriftarnema frá Íslenska Orkuháskólanum (ISE) við Háskólann í Reykjavík (HR), sem gefur ítarlega greiningu á faglegum framförum þeirra innan sjálfbærrar orku- og sjálfbærnisviðs á heimsvísu. Að nota blandaða nálgun og nýta megindleg gögn ...